Karma Phala As A Basis Of Belief In Maintaining Sustainability Financial Institutions (Study at Village Credit Institutions LPD) - Lestari, Ni Kadek Mita; Pradnyawati, Sagung Oka; Widhiastuti, Ni Luh Putu; Kusuma Dewi, Kadek Indah; Apri Ani, Ni Kadek Irdian (AIBPM Publisher, 2023)
Sustainability is one of the main goals of an institution. In a business, sustainability can be influenced by financial and non-financial aspects. In Hindu teachings there is a teaching about Karma Phala (cause and effect) where every action will return to us, this teaching helps individuals control their attitudes in the world. The author examines the belief in karma phala in the sustainability of a financial institution in Bali which is managed by a traditional village and is known as the Lembaga Perkreditan Desa (LPD). Data sources were obtained from observation and unstructured interviews. Qualitative methods are used descriptively and focus on the interpretation of human behavior. Data processing uses stages of reduction, presentation and drawing conclusions. Research shows that the teachings of karma phala have been attached to LPD supervisors, but there needs to be more emphasis on awareness of the role of supervisors in the sustainability of LPD and the profession. These results can remind us of the importance of karmic beliefs in carrying out a profession so that they are not only researched in LPD business continuity but also in other institutions.